El tratamiento de la metáfora en la traducción de Historias de Tata Mundo (LETRAS, 2014)
Fabián Dobles plantea mediante hechos característicos y regionalismos una imagen del campesino nacional de mediados de siglo xx en su obra Historias de Tata Mundo. Joan Henry lo traduce al inglés en 1998 y lo titula The Stories of Tata Mundo, transportando al campesino costarricense a la escena de habla inglesa. Se analizan las decisiones de la traductora sobre el tratamiento de las metáforas, teniendo en cuenta el lenguaje figurado como una herramienta empleada por el autor para caracterizar la vida rural del campesinado costarricense.Using traditional activities and regionalisms, Fabián Dobles reconstructed the image of the Costa Rican country folk of the mid-twentieth century in his literary work Historias de Tata Mundo. Joan Henry translated it in 1998, with the title The Stories of Tata Mundo, transporting the local peasant to the English-speaking scenario. The translator’s decisions are analyzed here regarding the translation of metaphors, taking into account figurative speech as a tool used by the author to characterize and depict the rural life of Costa Rican country folk.